1996
DOI: 10.1111/j.1365-3156.1996.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide‐treated bednets reduce mortality and severe morbidity from malaria among children on the Kenyan coast

Abstract: Summary New tools to prevent malaria morbidity and mortality are needed to improve child survival in sub‐Saharan Africa. Insecticide treated bednets (ITBN) have been shown, in one setting (The Gambia, West Africa), to reduce childhood mortality. To assess the impact of ITBN on child survival under different epidemiological and cultural conditions we conducted a community randomized, controlled trial of permethrin treated bednets (0.5 g/m2) among a rural population on the Kenyan Coast. Between 1991 and 1993 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(152 citation statements)
references
References 22 publications
9
140
3
Order By: Relevance
“…The community-wide impact of targeted control has not been studied extensively, although early controlled trials showed that bed nets were effective at reducing child morbidity and mortality associated with malaria, in villages or communities randomised to the intervention in The Gambia 30 and Kilifi 31 . More recent studies have shown that the use of bed nets in a village randomized to intervention in Asembo, western Kenya, also protected individuals just outside the intervention village who were themselves not using bed nets 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The community-wide impact of targeted control has not been studied extensively, although early controlled trials showed that bed nets were effective at reducing child morbidity and mortality associated with malaria, in villages or communities randomised to the intervention in The Gambia 30 and Kilifi 31 . More recent studies have shown that the use of bed nets in a village randomized to intervention in Asembo, western Kenya, also protected individuals just outside the intervention village who were themselves not using bed nets 32 .…”
Section: Introductionmentioning
confidence: 99%
“…arabiensis in Kenya. In the 1990s and early 2000s, insecticide-treated bednet (ITN) coverage in Kenya was generally low (Guyatt et al 2004), and large-scale ITN coverage and indoor residual spray were primarily concentrated in bed net trial areas or well-organized vector control areas (e.g., Nevill et al 1996;Bogh et al 1998;Hawley et al 2003, Lindblade et al 2006. Our survey found that occasional agricultural insecticide use in Kenya was primarily in the rice, coffee/tea plantation and sugar cane growing areas while other areas reported little use of insecticides .…”
Section: Discussionmentioning
confidence: 93%
“…Since the 1990s, pyrethroids have been promoted as insecticides of choice for bed net impregnation and indoor spray (WHO 1993) due to their high efficacy, rapid rate of knockdown, strong mosquito excitorepellency, and low mammalian toxicity (WHO 1993, Hemingway et al 2004, Liu et al 2006. As demonstrated in multi-site trials throughout Africa, the large-scale use of insecticide-treated bed nets (ITNs) reduces childhood malaria morbidity by up to 50% and overall mortality by 20-30% in Gambia, Ghana, and Kenya (Alonso et al 1991, Binka et al 1996, Nevill et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…By 1990, more than 500 species of insects and mites had developed resistance to one or more classes of insecticides (44). The use of ITNs for both individual and collective protection against malaria has shown potential in reducing childhood malaria morbidity by 50% and global mortality by 20-30% in the Gambia, Ghana, and Kenya (48)(49)(50). The insecticides of choice for bed net impregnation are pyrethroids because of their high efficacy, rapid rate of knockdown, strong mosquito excito-repellent properties, and low mammalian toxicity (51).…”
Section: Insect Resistance Development (Ird)mentioning
confidence: 99%